2006
DOI: 10.1083/jcb.200604150
|View full text |Cite
|
Sign up to set email alerts
|

BMP action in skeletogenesis involves attenuation of retinoid signaling

Abstract: The bone morphogenetic protein (BMP) and growth and differentiation factor (GDF) signaling pathways have well-established and essential roles within the developing skeleton in coordinating the formation of cartilaginous anlagen. However, the identification of bona fide targets that underlie the action of these signaling molecules in chondrogenesis has remained elusive. We have identified the gene for the retinoic acid (RA) synthesis enzyme Aldh1a2 as a principal target of BMP signaling; prochondrogenic BMPs or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 43 publications
8
108
0
2
Order By: Relevance
“…MDSCs have previously been shown to have chondrogenic potential (24,25), especially after BMP-4 transduction. BMP-4 has also been demonstrated to enhance potential for chondrogenesis in vitro and in vivo in cell types other than MDSCs (38)(39)(40). It has also been reported that the combined effect of TGF␤3 and BMP-4 or BMP-2 on chondrogenic pellet size is greater than that of each growth factor administered separately (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…MDSCs have previously been shown to have chondrogenic potential (24,25), especially after BMP-4 transduction. BMP-4 has also been demonstrated to enhance potential for chondrogenesis in vitro and in vivo in cell types other than MDSCs (38)(39)(40). It has also been reported that the combined effect of TGF␤3 and BMP-4 or BMP-2 on chondrogenic pellet size is greater than that of each growth factor administered separately (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Both Crabp2 and Raldh2 are also expressed interdigitally in mouse autopods (Niederreither et al, 1997;Ruberte et al, 1992), and syndactyly (fusion of the digits, extra phalanges) occurs in Crabp2 knockout mice (Lampron et al, 1995) suggesting that the normal function of RA at this stage is to keep developing digits separated. Raldh2 expression, and therefore RA synthesis, is restricted to interdigital regions in mice by the direct action of prochondrogenic BMPs, which attenuate Raldh2 expression (Hoffman et al, 2006).…”
Section: Complex Regulation Of Ra In Later Limb Development Sculpts Tmentioning
confidence: 99%
“…The activity of this reporter has been shown to tightly correlate with chondroblast differentiation and cartilage formation (Hoffman et al, 2006;Muramatsu et al, 2007;Weston et al, 2000). Col2-LUC reporter activity in Cyp26b1 -/-PLM cultures was around seven-times lower than that in the wild type after only 1 day of culture (Fig.…”
Section: Increased Retinoid Signalling Negatively Affects Chondrogenesismentioning
confidence: 99%